Pengaruh Green Marketing dan Brand Trust Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Sebagai Variabel Intervening: Studi pada Konsumen Generasi Milenial dan Gen Z di Fore Coffee Surabaya - Clarissa Diva Elvarreta; R. Yuniardi Rusdianto (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The rapid expansion of coffee shop businesses in Indonesia has intensified competition within the industry, making customer retention increasingly important for business sustainability. In this context, customer loyalty is shaped by multiple determinants, including environmentally oriented marketing practices and the level of trust in a brand. This research examines the role of green marketing and brand trust in influencing customer loyalty, with customer satisfaction acting as a mediating variable among Fore Coffee consumers in Surabaya. A quantitative approach was applied, and data were gathered from 100 respondents using a Likert-scale questionnaire through purposive sampling. The data were analyzed using descriptive statistics and path analysis with IBM SPSS version 25. The findings reveal that both green marketing and brand trust significantly enhance customer satisfaction. Nevertheless, customer satisfaction does not demonstrate a significant effect on customer loyalty. In addition, no significant indirect effects were found from green marketing and brand trust on customer loyalty through customer satisfaction. These results imply that customer loyalty formation may be driven by additional factors beyond satisfaction alone.